The Effects of Intersecting Stigma: A Longitudinal Examination of Minority Stress, Mental Health, and Substance Use among Black, Latino, and Multiracial Gay and Bisexual Men - English, Devin (Psychol Violence, 2018)
OBJECTIVE: Although Black, Latino, and multiracial gay and bisexual men (GBM) are disproportionately affected by health inequities facing GBM more broadly in the United States (CDC, 2017), there is a dearth of research examining how intersectional stigma affects psychological and behavioral outcomes such as depressive and anxiety symptoms and substance use. Based in minority stress and intersectionality theories, this study examined the main and intersectional effects of racial discrimination and gay rejection sensitivity on emotion regulation difficulties, depressive and anxiety symptoms, and later drug use and heavy drinking. METHOD: We collected longitudinal data from 170 GBM of Black, Latino, or multiracial descent. Measurements included baseline racial discrimination, gay rejection sensitivity, and emotion regulation difficulties, 6 month depressive and anxiety symptoms, and baseline to 12 month heavy drinking and drug use. We analyzed data using longitudinal structural equation models. RESULTS: Our results indicated that racial discrimination and its interaction with gay rejection sensitivity were significantly associated with higher levels of emotion regulation difficulties, which predicted higher levels of depressive and anxiety symptoms at 6 months, which, in turn, predicted higher levels of heavy drinking, but not drug use, at 12 months. Moreover, the total indirect effect from the stigma variables to heavy drinking was statistically significant. CONCLUSIONS: These findings indicate that it is critical for researchers and clinicians to consider the effects of intersecting racial and sexual minority stress on emotion regulation in the persistence of psychological and behavioral health inequities facing Black, Latino, and multiracial GBM.